Outcomes Following Revision Stapes Surgery in Children: A Single-Surgeon, Single-Center 15-Year Experience. Issue 6 (July 2020) - Jervis-Bardy, Joshua; Gau, Victoria L.; Allsopp, Tristan; King, Deanne; Page, Joshua Cody; Dornhoffer, John L.
Abstract : Objective: To review a single surgeon experience with revision pediatric stapes surgery for congenital stapes fixation (CSF) and tympanosclerosis (TS). Secondly, to determine whether hearing outcomes following revision surgery may be predicted by a thorough work-up aimed at assessing whether an extruded or malpositioned prosthesis is likely to be encountered intraoperatively. Setting: Tertiary referral center. Study Design: Retrospective chart review. Patients: Fifteen patients having revision surgery for fixation of the stapes footplate over a 15-year period. Main Outcome Measures: Hearing results based on pre- and post-revision pure-tone average air-bone gap (PTA-ABG) and speech recognition threshold testing (SRT). Results: Overall, the mean improvement of PTA-ABG following revision surgery was 11.9 dB (standard deviation [SD] 15.2) while SRTs improved by a mean of 12.3 (SD 19.9). Outcomes were significantly better in patients who reported a history of trauma following their initial surgery, when there was otoscopic evidence of an extruding or extruded prosthesis and/or a pre-revision CT (where performed) suggested an extruded or malpositioned prosthesis. No patients had a significant postoperative sensorineural hearing loss. Conclusion: Revision stapes surgery in children is a safe procedure in experienced hands which nonetheless should only be contemplated in patients in whom preoperative work-up suggests an extruded or malpositioned prosthesis is likely to be encountered intraoperatively.